Pengaruh Relationship Marketing Terhadap Kepuasan Pelanggan Pengguna Jasa Pengiriman Barang Pada CV Cipta Karya Sarana - Hutasoit, Merlin Yuliarti; Rosmita, Rosmita (SYNERGY: Jurnal Bisnis dan Manajemen, 2023)
Goods delivery services are companies engaged in service where service is the basis for costumer consideration in choosing goods delivery services. This research was conducted using two variables, namely Relationship Marketing (X) as the independent variable and Customer Satisfaction (Y) as the dependent variable. This study aims to determine and analyze the effect of Relationship Marketing on Customer Satisfaction at CV Cipta Karya Sarana. The results of this study indicate that the Relationship Marketing variable with indicators of trust, commitment, communication, and conflict handling gets results from respondents in the good category. As for the Customer Satisfaction variable with indicators, overall customer satisfaction, dimensions of customer satisfaction, confirmation and expectations, repurchase intentions, willingness to recommend getting results from respondents in the satisfied category. From the results of data analysis, the validity, reliability, t test, coefficient of determination test, and simple linear regression show that Relationship Marketing has a positive and significant effect on Customer Satisfaction.